Cosmopolitism in sponges: The ‘complex' Guitarra fimbriata with description of a new species of Guitarra from the northeast Atlantic. In: Uriz, M.-J. & Rützler, K. (Eds), Recent Advances in Ecology and Systematics of Sponges. - Boury-Esnault, N.; Pansini, M.; Uriz, M.J. (Scientia Marina, 1993)
A new species of the genus Guitarra (G. laplani) is described from the Gibraltar region (Northeast Atlantic). The type material of the species G. fimbriata Carter and G. voluta Topsent was revised by scanning electron microscopy, and the results compared with descriptions from the literature.The results suggest G. voluta is a valid species and provide grounds for distinguishing two groups of specimens among those described under the name G. fimbriata. The first group is formed by North Atlantic deep specimens matching the holotype of G. fimbriata and is mainly characterized by tornostrongyloid megascleres, the presence of two categories of placochelae, and microspined pseudoisochelae. The second group. with an lndo-Pacific littoral distribution, would correspond to G. bipocillifera Bronsted, characterized by oxeas tapering to long points as megascleres. one category of placochelae. and distinctive spiny isochelae. These results illustrate a new example of what was previously believed to be a cosmopolite species. that a thorough reexamination has shown to be a species complex. thus restricting thc distribution of G. fimbriata s.s. to the North Atlantic.
Proceedings of the 8th Workshop on Atlanto-Mediterranean Sponge Taxonomy